2006
DOI: 10.1103/physrevb.73.052505
|View full text |Cite
|
Sign up to set email alerts
|

Ginzburg-Landau theory of superconducting surfaces under the influence of electric fields

Abstract: A boundary condition for the Ginzburg-Landau wave function at surfaces biased by a strong electric field is derived within the de Gennes approach. This condition provides a simple theory of the field effect on the critical temperature of superconducting layers.The critical temperature of a thin superconducting layer is increased or lowered by an electric field applied perpendicular to the layer. [1][2][3][4][5] Similarly to the conductivity of inverse layers in semiconductors, superconductivity of thin metalli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…A different situation is met if the direction of the electric field is reversed. If L = 500 Å for the parameters of [14] we obtain T ⁎ − T c = 0.9 K in reasonable agreement with the reported shift by 1 K and the results of [9].…”
Section: Basic Equations and Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…A different situation is met if the direction of the electric field is reversed. If L = 500 Å for the parameters of [14] we obtain T ⁎ − T c = 0.9 K in reasonable agreement with the reported shift by 1 K and the results of [9].…”
Section: Basic Equations and Resultssupporting
confidence: 90%
“…In the one-band model [9], it can be shown that for |EL/ U s | = 6.9 the shift T ⁎ − T c = 0.1 K in the sample Sm 0.7 Ca 0.3 Cu 3 O y and is overdoped with T c ≈ 50 K. Matijasevic et al [14] reported no suppression of the superconductivity. The estimate in [9] shows that the suppression of the superconductivity T ⁎ − T c = 0.1 K is below the sensitivity of the measurement method [14]. A different situation is met if the direction of the electric field is reversed.…”
Section: Basic Equations and Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Apart from mentioned above acoustical and electromagnetic systems, complex extrapolation lengths can be realized for the superconducting materials too [1]. Namely, it was argued recently [80][81][82] that the electric field E applied perpendicularly to the surface should be accounted for in the total de Gennes distance Λ tot by the addition to the inverse zero-field extrapolation length 1/Λ of the extra term E/U s…”
Section: Introductionmentioning
confidence: 99%